Graphene-Gold Metasurface Architectures for Ultrasensitive Plasmonic Biosensing - Zeng, Shuwen; Sreekanth, Kandammathe Valiyaveedu; Shang, Jingzhi; Yu, Ting; Chen, Chih-Kuang; Yin, Feng; Baillargeat, Dominique; Coquet, Philippe; Ho, Ho-Pui; Kabashin, Andrei V.; Yong, Ken-Tye (Advanced materials (Weinheim), 2015)
Graphene–gold metasurface architectures that can provide significant gains in plasmonic detection sensitivity for trace‐amount target analytes are reported. Benefiting from extreme phase singularities of reflected light induced by strong plasmon‐mediated energy confinements, the metasurface demonstrates a much‐improved sensitivity to molecular bindings nearby and achieves an ultralow detection limit of 1 × 10−18 m for 7.3 kDa 24‐mer single‐stranded DNA.